2009
DOI: 10.1177/0047287509355322
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Use History: Exploring a New Framework for Understanding Residents’ Attitudes toward Tourism

Abstract: This study attempts to answer the question “What influence does an individual’s travel have on attitudes concerning who should develop tourism in their community as well as the role of the government in such development?” Research on residents’ attitudes toward tourism has traditionally focused on demographic, socioeconomic, and spatial predictor variables, with relatively few consistent findings. Based on the experience use history concept from the leisure and outdoor recreation literature, this study explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 42 publications
0
40
1
Order By: Relevance
“…However, mixed findings have developed, as no one socio-demographic variable has consistently yielded significant results (Harrill, 2004). This is likely explained by the fact that resident attitudes' studies are highly contextual, whereby not every community is homogenous in its composition of residents, exposed to the same phenomenon, and located in the same region across the globe (Draper, Woosnam, & Norman, 2009;Woosnam & Norman, 2010). In applying the social exchange theory, Ward and Berno (2011) found that gender, age, and employment (i.e.…”
Section: Social Exchange Theorymentioning
confidence: 99%
“…However, mixed findings have developed, as no one socio-demographic variable has consistently yielded significant results (Harrill, 2004). This is likely explained by the fact that resident attitudes' studies are highly contextual, whereby not every community is homogenous in its composition of residents, exposed to the same phenomenon, and located in the same region across the globe (Draper, Woosnam, & Norman, 2009;Woosnam & Norman, 2010). In applying the social exchange theory, Ward and Berno (2011) found that gender, age, and employment (i.e.…”
Section: Social Exchange Theorymentioning
confidence: 99%
“…Results are discussed in relation to the stage of tourism development in each destination. Further development and testing of tourism use history is recommended (Draper et al, 2011) …”
Section: Tourism Use History: Exploring a New Framework For Understanmentioning
confidence: 99%
“…Despite the diversity of approaches and content, research developed in this field shares the utilization of a predefined set of independent variables (Huh & Vogt, 2008;Draper, Woosnam & Norman, 2011) adopted to predict the perceptions of residents towards tourism, such as the traditional socio-demographic dimensions (e.g. age, gender, education, length of residence, ethnicity), socio-economic (income and economic dependence in tourism activities); those most closely linked to the geographical space-dimension (e.g.…”
Section: Review Of Literaturementioning
confidence: 99%